2007
DOI: 10.1080/09712119.2007.9706662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slaughter Age on Fattening Performance and Carcass Characteristics of Japanese Quails (Coturnix coturnix japonica)

Abstract: Seker, I., Bayraktar, M., Kul, S. and Ozmen, 0. 2007. Effect of slaughter age on fattening performance and carcass characteristics of Japanese quails (Coturnix coturnix japonica). J . Appl. Anim. Res., To determine the most economic slaughter age for male Japanese quails a total of 220 quail chicks were fed a standard feed up to 49 days. Rate of live weight gain started decreasing after 28 days of age. Feed consumption showed similar trend after d35. However, the feed required for each gram of weight gain exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 4 publications
9
17
0
Order By: Relevance
“…Our results bring new and extend existing knowledge on quality of muscle protein in six feathered game species bred under European conditions. They further support findings pointing out high slaughter value of feathered game, especially common pheasant (Tucak et al, 2008;Franco and Lorenzo, 2013), grey partridge (Gaglianone Moro et al, 2006), quail (Seker et al, 2009;Bednarczyk et al, 2007), guinea fowl (Nahashon et al, 2009) and chukar partridge (Özek et al, 2003;Esen et al, 2006). It may be said that with regard to AAs feathered game muscle is a significant source of quality protein, especially for its higher levels of essential amino acids.…”
Section: Ii: Mean Values (X ± Sd) Of Total Amino Acid Levels Levels supporting
confidence: 76%
See 1 more Smart Citation
“…Our results bring new and extend existing knowledge on quality of muscle protein in six feathered game species bred under European conditions. They further support findings pointing out high slaughter value of feathered game, especially common pheasant (Tucak et al, 2008;Franco and Lorenzo, 2013), grey partridge (Gaglianone Moro et al, 2006), quail (Seker et al, 2009;Bednarczyk et al, 2007), guinea fowl (Nahashon et al, 2009) and chukar partridge (Özek et al, 2003;Esen et al, 2006). It may be said that with regard to AAs feathered game muscle is a significant source of quality protein, especially for its higher levels of essential amino acids.…”
Section: Ii: Mean Values (X ± Sd) Of Total Amino Acid Levels Levels supporting
confidence: 76%
“…Several authors studied chemical composition of various parts of partridge body (Gaglianone Moro et al, 2006), slaughter value of quails, effect of gender on indicators of yield and slaughter value of quails with the conclusion that separate breeding of genders may be more beneficial (Kul et al, 2006). Effect of the size of groups of quails on feeding parameters and slaughter value was studied (Seker et al, 2009) together with the effect of supplementation of L-carnitine in quail diet on growth, slaughter value and composition of quail meat (Sarica et al, 2005). Nutritional and sensory value of quail meat was also studied (Bednarczyk et al, 2007), as well as the level of nutrition and its effect on production and slaughter indicators in chukar partridge (Özek et al, 2003) and the effect of the number of animals per cage on their slaughter characteristics (Esen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, positive correlations between egg weight and chick hatch weight have been reported (Ojo et al, 2012), larger egg size in the Brown variety may therefore be of advantage in quail breeding industry. The values obtained in this study for quail egg weight are however similar to those reported by Dudusola, (2010) and Ojo et al (2011) but lower than the values reported by Seker et al (2005) andSezer, (2007). Positive relationship have been reported between body weight and egg weight in many breeds of poultry (Ayorinde et al, 1988;Sola-Ojo et al, 2011 andOjo et al, 2011) the lower egg weight reported in this study may therefore be as a result of the characteristic lower body weight of the birds in this region compared to those in other studies.…”
Section: Discussionsupporting
confidence: 56%
“…Dressing percentage was higher in 42-day-old birds but the difference between the analysed groups was not significant. In another study, Seker et al [17] also obtained higher dressing percentage in older quails. In 42-day-old quail, Kluczek [9] found dressing percentage (61.1%) to be lower than in our study.…”
Section: Resultsmentioning
confidence: 79%